Relapsing Polychondritis: Case Report and Review of the Literature (Journal of Medicine, 2014)
Relapsing polychondritis is a rare, severe, episodic and progressive inflammatory disorder of unknown aetiology and autoimmune pathogenesis, causing recurrent inflammation of involving cartilaginous structures, predominantly those of the ears, nose, and laryngotracheobronchial tree. Rarity of this disease, array of many possible presenting symptoms, lack of specific diagnostic investigation and episodic nature often causes significant delay in diagnosis. We are reporting a 55 year old woman presenting with recurrent episodes of pain, swelling, redness of nose, and both ear resulting in depressed nasal bridge and floppy pinna. Relapsing polychondritis was diagnosed and she was treated with systemic corticosteroid successfully.DOI: http://dx.doi.org/10.3329/jom.v15i1.19881 J Medicine 2014; 15: 80-83